Promoting resilience among expectant and parenting youth in California during the COVID-19 pandemic - Yalda Toofan; Lia Cassanego; Shira Rutman; Kathleen P Tebb (Archives of Nursing Practice and Care - Peertechz Publications, 2020)
The purpose of this study is to showcase some of the challenges experienced with the transition to and implementation of televisits and to identify strategies both in terms of practice and policy that enhance case managers' ability to connect, engage and continue to support expectant and parenting youth (EPY) during the COVID-19 pandemic. A total of 83 program staff (case managers and supervisors) from each of the 20 programs across California provided information on their experiences in serving EPY youth during this challenging time, especially as they transitioned from traditional face to face visits to online televisits. They report that COVID has exacerbated the challenges facing expectant and parenting youth and identified a number of challenges in conducting televisits. Case managers provide critical support for EPY, understanding the needs of and providing ongoing support for these front-line staff is essential during this pandemic.